Controllable Multinary Alloy Electrodeposition for Thin-Film Solar Cell Fabrication: A Case Study of Kesterite Cu(2)ZnSnS(4) - Ge, Jie (iScience, 2018)
Electrodeposition (ED) technology is a low-cost industrial candidate for solar cell fabrication. However, the practical aspects of controlling deposit morphology and composition have not been significantly addressed because of the complex co-plating variables that still need to be understood for multinary alloy ED. This work addresses these practical aspects on how to control composition and deposit morphology using co-electrodeposited kesterite alloy precursors as a case study. The alloy precursors co-plated under the optimized conditions from a mixed thiosulfate-sulfite electrolyte bath show uniform, smooth, and compact film morphology as well as uniform distribution of composition, well suited for efficient kesterite absorbers, finally delivering a Cu(2)ZnSnS(4) (CZTS) thin-film solar cell with 7.4% efficiency based on a configuration Mo/CZTS/CdS/ZnO/aluminum-doped ZnO. This work underscores that alloy ED, with the advantage of controllable composition and morphology, holds promise for low-cost industrial manufacture of thin-film solar cells.